2009
DOI: 10.1016/j.epidem.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Saprophytism of a fish pathogen as a transmission strategy

Abstract: Fish farming creates conditions where disease transmission is enhanced and antibiotic treatments are commonly used to cure bacterial diseases to prevent severe losses due to infections. Ability to persist in such an environment has been suggested to lead to the evolution of high virulence. Columnaris disease caused by Flavobacterium columnare is a growing problem in freshwater fish farming. Transmission of the disease is poorly known, and survival of F. columnare in the rearing environment has not been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…Thus, if the bacteria are tuned to make the most of the animalbased resources, they could be more efficient in using the same energy source in the immediate future [7]. This could lead to a situation where previous exposure to animal-based resources, for example through saphrophytism [22], facilitates the pathogen's virulence in an animal host. It is unlikely that 48 h would be a time span long enough for genetic changes to increase to a detectable frequency, and de novo mutations to explain the results.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, if the bacteria are tuned to make the most of the animalbased resources, they could be more efficient in using the same energy source in the immediate future [7]. This could lead to a situation where previous exposure to animal-based resources, for example through saphrophytism [22], facilitates the pathogen's virulence in an animal host. It is unlikely that 48 h would be a time span long enough for genetic changes to increase to a detectable frequency, and de novo mutations to explain the results.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the growth of F. columnare was completely inhibited by 10 ppt NaCl (40, 41), but we observed bacterial growth at salinities as high as 14 ppt NaCl, which might be explained by the use of different culture conditions. F. columnare can survive for long periods in distilled water (11,12), but calcium has a positive effect on both its survival (42) and its growth (43). A calcium carbonate hardness of 70 ppm is considered optimum for F. columnare growth, while levels lower than 50 ppm have been shown to decrease its survival (44).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its economic impact, the ecological niche of F. columnare has not been clearly identified although most studies point to fish as the primary disease reservoir (8,9). However, fish-to-fish contact is not required for disease transmission (10) and the long-term survival of F. columnare in lake water suggests that water can be the main reservoir of this pathogen (11). In a recent study, we have shown that although F. columnare can survive in water without nutrients for extended periods, its cells underwent drastic morphological changes that resulted in loss of fitness over time (12).…”
mentioning
confidence: 99%
“…Flavobacteria might also utilize a "switch on-off" mechanism which involves environmental control of adhesins or receptors associated with the bacterial surface in direct relation to nutri-tional and possibly quorum-sensing cues. Given their saprophytic nature (Kunttu et al, 2009), Flavobacterium spp. are not only transmitted from dead fish to live fish, but are also capable of surviving long periods in water outside the fish host.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Flavobacterium are known to form biofilms (Álvarez et al, 2006;Basson et al, 2008), not only as a stress response but as an adaptation to allow persistence of cells on the outer surface of the fish host during the early stages of infection (Staroscik and Nelson, 2008) or to survive as saprophytes in the fish farm environment (Kunttu et al, 2009). Adhesion to the host's surface is an essential step in the primary colonization of the host by a pathogenic bacterium, and pathogenic Flavobacterium spp.…”
Section: Introductionmentioning
confidence: 99%